Diffuse Granulomatous Conjunctivitis as an Ocular Manifestation of ANCA-Negative Limited Wegener’s Granulomatosis: A Case-Based Literature Review - Hartono, Cindy; Pratiwi, Andi; Sungowati, Ni Ketut; Fikri, Bahrul; Eka, Hasnah (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2025)
Introduction: Necrotizing granulomatous vasculitis, which is commonly known as Wegener's Granulomatosis (WG), frequently affects small to medium-sized blood vessels and is associated with anti-neutrophil cytoplasmic antibodies (ANCA). Despite ocular manifestations being prevalent in the disease, initial symptoms involving the eyelid and conjunctiva are infrequent. This study reports a case of an 11-year-old girl diagnosed with localized WG in the conjunctiva, with negative ANCA-test, and biopsy strongly suggested WG. Case Report: An 11-year-old girl presented a red membrane covering the entire ocular surface and diminished vision in the left eye seven months before admission. At presentation, hand motion in the left eye was the best corrected visual acuity. There were granuloma formations in the palpebral and bulbar conjunctival, covering the entire ocular surface in the left eye. An incisional biopsy was performed in the conjunctiva, which revealed an ulcerative mucous membrane, prominent vasculitis, and necrotizing granulomas with giant cells and massive leukocyte infiltrate consistent with WG diagnosis. Discussion: There is a need to consider the clinical manifestations suggesting the presence of vasculitis, ANCA determination, and histopathological evidence of the compromised organ to confirm the diagnosis. Overall, 82-94% of patients with WG were ANCA positive, leaving approximately 10% who tested negative, particularly those with limited WG. Moreover, a biopsy can confirm the diagnosis, specifically in ANCA-negative cases. Conclusion: This case illustrated the consideration for WG diagnosis in limited form and negative ANCA-test. The clinical suspicion of WG and alternative diagnostic criteria using tissue biopsy might be helpful in such cases.